Assessing processing speed among individuals with intellectual and developmental disabilities: A match-to-sample paradigm. Issue 1 (2nd January 2022) - Kaat, Aaron J.; McKenzie, Forrest J.; Shields, Rebecca H.; LaForte, Erica; Coleman, Jeanine; Michalak, Claire; Hessl, David R.
ABSTRACT: Speeded Matching (SpM) is a new processing speed match-to-sample test within the NIH Toolbox Cognitive Battery. It was designed to developmentally extend feasibility to younger children or individuals with intellectual or developmental disabilities (IDD). SpM reduces cognitive demands to tapping an identical match as opposed to judging and indicating whether two stimuli are identical. In this study, we piloted SpM among 148 participants with fragile X syndrome, Down syndrome, or other intellectual disabilities (chronological age mean = 17.8 years, sd = 5.4; nonverbal mental age mean = 65 months, sd = 19.4). SpM had a high feasibility (96%) and internal consistency (rxx = 0.98). It converged well with other measures of processing speed, fluid cognition, and nonverbal mental age and diverged appropriately from crystallized cognitive skills. The correlation between nonverbal mental age and SpM in the IDD sample was not significantly different than the correlation between chronological age and SpM in a separate sample of 118 neurotypical children (age mean = 3.9 years sd = 0.8). This study provides initial evidence for the reliability and validity of the new SpM task, which may be appropriate as an outcome measure of processing speed for future clinical trials. It is more feasible than tasks designed for adults; it is brief, easy to administer, and engaging for young children and older individuals with lower mental ages associated with IDD.